2009
DOI: 10.1203/pdr.0b013e3181a9d80c
|View full text |Cite
|
Sign up to set email alerts
|

Staphylococcus epidermidis Isolated From Newborn Infants Express Pilus-Like Structures and Are Inhibited by the Cathelicidin-Derived Antimicrobial Peptide LL37

Abstract: Coagulase-negative staphylococci and its subtype Staphylococcus epidermidis are major indigenous Gram-positive inhabitants of the human skin. Colonization occurs in direct connection with birth and terrestrial adaptation. This study focuses on factors that may influence skin colonization of the newborn infant that relates to the immune status of both the bacteria and the host. Skin is an effective barrier against bacteria, and this function is partly mediated by the presence of antimicrobial peptides including… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
26
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(27 citation statements)
references
References 28 publications
(28 reference statements)
1
26
0
Order By: Relevance
“…The inactivity of LL-37 against S. aureus and S. epidermis is consistent with other studies [64]. However, the anti-microbial effect of LL-37 on Staphylococcus could be strain dependent as several studies have reported an effect of this peptide on both S epidermis [65] and S. aureus [66], [67]. Despite structural similarities with the mammalian peptides tested, none of the HDMs demonstrated bactericidal activity against any species of bacteria at the concentrations tested (<0.25 to 128 µg/ml).…”
Section: Resultssupporting
confidence: 90%
“…The inactivity of LL-37 against S. aureus and S. epidermis is consistent with other studies [64]. However, the anti-microbial effect of LL-37 on Staphylococcus could be strain dependent as several studies have reported an effect of this peptide on both S epidermis [65] and S. aureus [66], [67]. Despite structural similarities with the mammalian peptides tested, none of the HDMs demonstrated bactericidal activity against any species of bacteria at the concentrations tested (<0.25 to 128 µg/ml).…”
Section: Resultssupporting
confidence: 90%
“…Staphylococcus epidermidis ATCC35984 strain did not produce biofilm in BM2 minimal medium (Overhage et al. 2008), and LL37 did not inhibit biofilm formation in combined MHB (Mueller Hinton Broth; Nelson et al. 2009), in our hands.…”
Section: Discussionmentioning
confidence: 46%
“…Peptide LL37 was purchased from Innovagen (Lund, Sweden). Distilled water contained 0·05% acetic acid was used for the dilutions of LL37 to prevent the precipitation of the peptide (Nelson et al. 2009).…”
Section: Methodsmentioning
confidence: 99%
“…Moreover, it was reported that Aap is fibrillar adhesion [15]. Nelson et.al reported that fibrinogenbinding protein Fbe and accumulation-associated protein Aap play major roles in the adherence of cells to accumulative growth on the polymer surface [14].…”
Section: Structural Observation Of Biofilm Formationmentioning
confidence: 99%
“…Especially, Staphylococcus epidermidis is well known as a commensal microorganism of human skin, nares, and mucous membranes [12,13]. Although fibrillar structures of S. epidermidis have been observed [11,14,15], observations of the ultrastructure of fibrils and detailed information on biofilm formation have not been reported till date.…”
Section: Introductionmentioning
confidence: 99%